Emergency Rescue Platform of Electric Vehicles Based on Natural Selection PSO - Wang, Ying Hui; Chu, Yi; Liu, Hua Feng; Lu, Zhi Yuan (Applied Mechanics and Materials, 2013)
Emergency rescue platform of electric vehicles based on natural selection PSO